KEANEKARAGAMAN DURIAN (Durio zibethinus Murr.) DI PULAU BENGKALIS BERDASARKAN KARAKTER MORFOLOGI - Lestari, Sri; Fitmawati, Fitmawati; Nihayatul Wahibah, Ninik (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2011)
Bengkalis Island is one of the areas with high diversity of durian (Durio zibethinus Murr.). This research was aimed to analyze the diversity ofÂ durian cultivars of Bengkalis Island. It was conducted from April up to August 2010. The morphological data were analysed using NTSYS-pc 2.02 and minitab 14.13 softwares. Genetic similarity value among 36 accesions ranged from 0,28 (between BT 14, BT 15 and SB6) to 0,66 (between BT6 and BT7). The cluster analysis showed that durian diversity from Bengkalis island was 34-58% or had similarity level 42-66% and formed 7 main groups. However, they were ungroupped depend on their growth areas. Based on PCA (Principal Components Analysis) value, durian diversity was 99,7% and formed 6 groups. Â Furthermore, the result of pearson correlation analysis among 77 character showed that 10 characters were positively correlated and 4 characters were negatively correlated.